การพัฒนาโปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ ในวัยรุ่นอาชีวศึกษา; Development Program to Reduce Alcohol Drinking in the adolescence Vocational Students - ลีวิโรจน์ พรรณปพร (Journal of Humanities and Social Sciences (HUSOKKU), 2017)
บทความนี้มีวัตถุประสงค์ เพื่อศึกษาความสัมพันธ์ระหว่างความฉลาดทางอารมณ์กับการดื่มเครื่องดื่มแอลกอฮอล์ การพัฒนาโปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ในวัยรุ่น และศึกษาผลการพัฒนาโปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ในวัยรุ่น เป็นการวิจัยเชิงปริมาณและเชิงทดลอง ในกลุ่มตัวอย่างวัยรุ่นอาชีวศึกษาในจังหวัดสมุทรปราการ จำนวน 1,132 คน เป็นทั้งผู้ดื่มและไม่ดื่มเครื่องดื่มแอลกอฮอล์ และคัดกรองกลุ่มที่ดื่มแบบเสี่ยงสูง เข้ากลุ่มทดลอง จำนวน 15 คนและกลุ่มควบคุม 15 คน มีการทดสอบก่อนการทดลอง หลังการทดลองและติดตามผล เครื่องมือในการวิจัยประกอบด้วย โปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ในวัยรุ่น แบบวัดความฉลาดทางอารมณ์และแบบคัดกรองการดื่มเครื่องดื่มแอลกอฮอล์ วิเคราะห์ข้อมูลด้วย Chi-Square และ t-test ได้ผลการวิจัย ดังนี้ 1) การดื่มเครื่องดื่มแอลกอฮอล์มีความสัมพันธ์กับความฉลาดทางอารมณ์ ในด้านการสร้างแรงจูงใจ การรับรู้อารมณ์ผู้อื่น ทักษะทางสังคมและการแก้ไขปัญหา 2) ได้โปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ในวัยรุ่น ประกอบด้วย 3 ขั้นตอน 10 กิจกรรม จำนวน 10 ครั้งๆ ละ 60-90 นาที สัปดาห์ละ 1 ครั้ง รวม 10 สัปดาห์ 3) ผลโปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ในวัยรุ่น พบว่า กลุ่มทดลองเมื่อเข้าโปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ มีปริมาณการดื่มเครื่องดื่มแอลกอฮอล์ลดลงกว่ากลุ่มควบคุม และมีความฉลาดทางอารมณ์สูงกว่ากลุ่มควบคุม อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ฉะนั้น โปรแกรมลดการดื่มเครื่องดื่มแอลกอฮอล์ ที่ผู้วิจัยได้สร้างขึ้นสามารถลดการดื่มเครื่องดื่มแอลกอฮอล์ได้ Abstract This article aimed to study the relations between emotional intelligence and alcohol drinking, the development program to reduce alcohol drinking in the adolescence and study to the effect of a program to reduce alcohol drinking in the adolescence, which are quantitative and experimental researches. The participants consisted of 1,132 vocational students in Samut-Prakarn Province who were used alcohol and disused alcohol, and classified as problem drinker or hazardous drinking. The participants were simple random sampling assigned into experimental and control groups. There were 15 hazardous drinkers in the experimental group and 15 hazardous drinkers in the control group.This research was research designed pretest, posttest, control group and follow up design. The instruments in the study were Program to Reduce Alcohol Drinking in the adolescence, questionnaires comprising Emotional Intelligence and Alcohol Use Disorders Identification Test (AUDIT). The data were analyzed by Chi-Square and t-test. The results of this research were as follows: 1) Drinking issues relate to emotional intelligence of self-motivation, social-awareness, social skills and problem solving. 2) The development program to reduce alcohol drinking in the adolescence, which comprised 3 steps, 10 group activities, 10 times, 60-90 minutes for each, once a week and continuously for 10 weeks. 3) The effect of program to reduce alcohol drinking. As a result of the experiment, it revealed that after the samples in experimental group attended the program to reduce alcohol drinking in the adolescence, the quantity of alcohol drinking has decreased more than those in the controlled group and their emotional intelligence has also been higher were statistically significant at the 0.05. Thus, the program to reduce alcohol drinking that the researcher has created can actually decrease alcohol drinking behaviors.